Peran Return on Equity, Debt to Equity Ratio dan Cash Ratio dalam Mempengaruhi Dividend Payout Ratio pada Perusahaan Go-Publik Sektor Barang Konsumsi Tahun 2014-2018 - Meliana Meliana; Wirda Lilia; Siska Siska; Andreas Andreas (Jurnal Samudra Ekonomi dan Bisnis, 2020)
The study aims to analyze the role of Return on Equity, Debt to Equity Ratio and Cash Ratio in influencing Dividend Payout Ratio on go-public companies of consumer goods sector in the year of 2014-2018. This quantitative-desciptive research sourced from financial data on the Indonesia Stock Exchange website. 18 companies were selected as a sample purposively from 47 companies in the consumer goods sector that were members of the population. The results showed that partially, Return on Equity and Debt to Equity Ratio were proven to have a significant role in influencing Dividend Payout Ratio; while Cash Ratio is proven to have no significant effect on Dividend Payout Ratio. Simultaneously, Return on Equity, Debt to Equity Ratio and Cash Ratio were proven to have a significant role in influencing Dividend Payout Ratio.